IMITASI DAN TRANSFORMASI BUDAYA NGUBEK SITU DALAM KARYA TARI RENGKAK AYAKAN MENURUT PERSPEKTIF SUSANNE K. LANGER - Marsya Frista, Nona; Nursilah; Selly Oktarini (Jurnal Pendidikan Tari, 2025)
This research discusses the process of imitation and transformation of the NgubekSitu tradition into the dance work Rengkak Ayakan, from the perspective of SusanneK. Langer. Rengkak Ayakan is a form of art inspired by community traditions,creatively processed into a symbolic expression of human emotion. According toLanger's theory, art is not merely a copy of reality, but the result of imitation andtransformation that creates symbolic meaning from felt emotions. This studyemploys a descriptive qualitative method, using observation, literature review, andin-depth interviews with choreographers, dancers, community figures, musicians,and the management of Sanggar Tari Gandes Pamantes. The results show thatRengkak Ayakan does not simply replicate the physical activities of a tradition, butrather interprets values of togetherness, joy, and gratitude through elements ofmovement, costume, props, and performance structure. This transformation resultsin a dance work that symbolically represents the meaning of the Ngubek Situtradition, in accordance with Langer’s concept of emotional expression. This,Rengkak Ayakan becomes an effective medium for cultural preservation byintegrating traditional elements with artistic creativity, and bridging local culturalheritage with the context of modern performance through a symbolic and expressiveapproach.